Reconciliation of roles : women, work, and family in Sri Lanka - Kiribamune, Sirima; International Centre for Ethnic Studies (New Delhi : International Centre for Ethnic Studies in association with NORAD and Navrang, 1993)
Contributed articles.
Keywords: Women -- Employment -- Sri Lanka -- History; Work and family -- Sri Lanka